How to be an Amazing Teacher - Bentley-Davies, Caroline (Karachi Paramount Books, 2018)
In most of our school experience there was an amazing teacher - the teacher who changes our outlook on life, helped us succeed and whose lessons we will never forget. What made them that outstanding teacher and what are the tips and techniques and tactics that make some teachers really first class? How do I improve my skills? How can I get behaviour right? How can I motivate pupils who don't seem to want to learn? Carefully blending practical advice, real life scenarios and expert opinion this book will make any teaching career more rewarding.
Include Index
Keywords: Teachers--Job satisfaction -- Teaching -- Great Britain